Preparation of Expandable Graphite Intercalated by Sulfuric Acid and Sodium Silicate and Its Flame Retardancy Application for Ethylene Vinyl Acetate Copolymer - Pang, Xiu-Yan; Tian, Yu; Zhai, Zhi-Xiao; Duan, Ming-Wei (Asian Journal of Chemistry, 2014)
Expandable graphite intercalated by sulfuric acid and sodium silicate (Na2SiO3) was prepared by two step intercalation method under oxidation of KMnO4. The influence of various factors on dilatability of the expandable graphite were discussed including the dosages of KMnO4, H2SO4, Na2SiO3·9H2O and H2SO4 concentration, pH of Na2SiO3 and NaOH mixed solution, reaction temperature, reaction time. Expandable graphite with an initial expansion temperature of 202 °C and expansion volume of 517 mL/g could be prepared under the mass ratio C:KMnO4:H2SO4 (98 %):Na2SiO3·9H2O of 1.0:0.22:4.0:0.8. H2SO4 should be diluted to mass concentration of 75 % before intercalation, Na2SiO3 dissolved in NaOH aqueous solution with a pH of 13 was dropwise added when the intercalation of H2SO4 preceded 7.5 min and the reaction was totally maintained 40 min at 40 °C. X-ray powder diffraction analysis was performed to illuminate the structure characteristics of expandable graphite and its flame retarding property for ethylene vinyl acetate copolymer (EVA) was investigated and characterized by limiting oxygen index (LOI) and scanning electron microscope. The LOI of EVA is only 19.3 %; addition of 30 % expandable graphite made the LOI of EVA/expandable graphite reaches 28.4 %, but the addition of same dosage of compared blank expandable graphite only get a LOI of 24.4 %. The excellent anti-flame capability of expandable graphite is owing to its fully endothermic expansion and formation of heat insulation swollen multicellular char.